An essential role for Rab27a GTPase in eosinophil exocytosis - Kim, John Dongil (Society for Leukocyte Biology, 2013)
Eosinophil degranulation has been implicated in inflammatory processes associated with allergic asthma. Rab27a, a Rab-related GTPase, is a regulatory intracellular signaling molecule expressed in human eosinophils. We postulated that Rab27a regulates eosinophil degranulation. We investigated the role of Rab27a in eosinophil degranulation within the context of airway inflammation. Rab27a expression and localization in eosinophils were investigated by using subcellular fractionation combined with Western blot analysis, and the results were confirmed by immunofluorescence analysis of Rab27a and the granule membrane marker CD63. To determine the function of eosinophil Rab27a, we used Ashen mice, a strain of Rab27a-deficient animals. Ashen eosinophils were tested for degranulation in response to PAF and calcium ionophore by measuring released EPX activity. Airway EPX release was also determined by intratracheal injection of eosinophils into mice lacking EPX. Rab27a immunoreactivity colocalized with eosinophil crystalloid granules, as determined by subcellular fractionation and immunofluorescence analysis. PAF induced eosinophil degranulation in correlation with redistribution of Rab27a(+) structures, some of which colocalized with CD63(+) crystalloid granules at the cell membrane. Eosinophils from mice had significantly reduced EPX release compared with normal WT eosinophils, both in vitro and in vivo. In mouse models, Ashen mice demonstrated reduced EPX release in BAL fluid. These findings suggest that Rab27a has a key role in eosinophil degranulation. Furthermore, these findings have implications for Rab27a-dependent eosinophil degranulation in airway inflammation.